Effect of the physical environment on toddlers’ groups in early child care (Training and Practice : Journal of Educational Sciences, 2019)
Nowadays, there is a great emphasis on environmental education, even in early child care. Too many stimuli can be as negative as too few. The research examines the effect of the differently designed physical environment on toddlers’ play activities. Children from 16 to 38 months of age in two differently designed early child care rooms were observed. In both groups 10-10 times, 30 minutes per occasions during the morning free play period. We used log-like data recording method, and also the modified BOMI TCRU observation guide. In addition, we photographed the location of children's play activities in the room every five minutes. While in the traditional group there was a less balanced atmosphere, in the jungle-group almost every time children played peacefully and harmoniously. In the jungle room, children make better use of creatively furnished spaces.